Failure of Fenbedazole and Ivermectin to Control Gastrointestinal Nematodes in Goats in Rewa, Madhya Pradesh - Chaurasiya, Rupesh; Dixit, Pooja; Dixit, Alok K (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Anthelmintic resistance has been reported in most goat-raising areas in India, yet little is known about the anthelmintic resistance status in gastrointestinal nematodes in goats in Rewa, Madhya Pradesh. The aim of this study was to determine the occurrence of anthelmintic resistance in goats in field conditions using Faecal Egg Count Reduction test (FECRT). 40 goats having egg per gram above 600 were divided into a control (G1) and three treatment groups (G2, G3 and G4) consisting of 10 goats in each group. Goats which were not given any treatment were kept as control group. Group G2, G3 and G4 goats were treated with fenbendazole @ 7.5 mg/kg BW orally, closantel @ 10 mg/kg BW orally and ivermectin @ 0.2 mg/kg BW subcutaneously, respectively. Percent reduction in faecal egg counts were monitored 14 days after treatment. The FECRT indicated percent reductions of 83, 94 and 94 for G2, G3 and G4, respectively. When analysed statistically using standard WAAVP protocol, anthelmintic resistance against fenbendazole and ivermectin was detected. These findings strongly suggest that anthelmintic resistance is a serious problem in strongyles in goats in Rewa and marked changes in gastrointestinal nematode management need to be instituted immediately to mitigate a worsening situation.